2016
DOI: 10.1021/acs.energyfuels.6b01241
|View full text |Cite
|
Sign up to set email alerts
|

What Is Behind the High Values of Hot Filtration Test of the Ebullated Bed Residue H-Oil Hydrocracker Residual Oils?

Abstract: This work summarizes the results of multiple experiments performed in the LUKOIL Neftohim Burgas Research Laboratory related to the issue of high values of hot filtration test (HFT) of the residue H-Oil hydrocracking residual oil products. After the start-up of the new residue H-Oil hydrocracker in the LUKOIL Neftohim Burgas refinery during the second half of 2015 the values of the HFT of the vacuum tower bottom product varied between 0.01 and 8.7%. It was found that the vacuum residual oil feed source has a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…Case 2 ( Table 2 ) is characterized by an extremely high sediment content in the hydrocracked ATB, and a 2-day operation at the conditions of case 2 was sufficient to shut down the ebullated-bed hydrocracker for 2 weeks for cleaning of the equipment. 59 By not being in operation for 1 day, the ebullated-bed hydrocracker experiences a loss of about 600 KUSD/day. 61 Except for case 2, all other 11 cases are characterized with the hydrocracked ATB sediment content not higher than 0.4%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Case 2 ( Table 2 ) is characterized by an extremely high sediment content in the hydrocracked ATB, and a 2-day operation at the conditions of case 2 was sufficient to shut down the ebullated-bed hydrocracker for 2 weeks for cleaning of the equipment. 59 By not being in operation for 1 day, the ebullated-bed hydrocracker experiences a loss of about 600 KUSD/day. 61 Except for case 2, all other 11 cases are characterized with the hydrocracked ATB sediment content not higher than 0.4%.…”
Section: Resultsmentioning
confidence: 99%
“…A simplified process diagram of the LNB EBR hydrocracker with the typical range of the operating condition variations is presented in ref ( 59 ). The catalyst employed in this study was a commercial Ni–Mo low sediment catalyst.…”
Section: Methodsmentioning
confidence: 99%
“…This suggests that the thermal aging facilitates the processes of agglomeration of the particles for those residual oils which are colloidal unstable. In our earlier study, it was found that in the H-Oil residual oils obtained from the LNB H-Oil residue hydrocracker the sediments are formed mainly due to aggregation of the insoluble asphaltenes (Stratiev et al, 2016b). Therefore, a conclusion could be made that the thermal aging procedure favours further the processes of agglomeration of the aggregated insoluble asphaltenes in the H-Oil residual oils.…”
Section: Saturates Asphaltenes CIImentioning
confidence: 94%
“…Sa is related to the solubility of the asphaltenes, the length and number of the aromatic chains), and So (peptising power of oil is the 'aromatic' equivalent of the oil; it is a measure of the solvency power of the oil with respect to asphaltene solubility) were measured by the use of a modification to ASTM D7157-05 as described in Bartholdy and Andersen (2000). Stratiev in his work showed that according to the oil compatibility model of Wiehe oils whose S-value ≥ 1.4 should be considered colloidal stable, which are not prone to form sediments (Stratiev et al, 2016b). The colloidal stability parameter SN of the investigated residual oils was measured in accordance with the ASTM D7061.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation